MARKET FAILURE AND ECONOMIC REGULATION: DOES THE GOVERNMENT REGULATION ALLOWS EXERCISED TO ACHIEVE A BETTER MARKET PERFORMANCE? - Rodríguez Cairo, Vladimir (2013)
The economic regulation has legal restrictions that impose to the agents that were involved in the market (like for example, the market of goods and services or the capital markets). However, there is an aspect relevant in the regulation we need to justify the present of the market failures that appear from the presents of the externalities, existence of public assets, failing competition, asymmetries and incomplete markets information. That is way, there is mayor consent in the market and the private companies cooperated to the accomplishment of economy. That way the government makes a very important role in the market. However the government keeps doing a controversy subject in ideological conflict of world. That why this article examines the background and fundamentalism, the failure the adjustment of the economy on the market, also the balance between market and government has a big role in the economy.